Portuguese traditional timber structures: survey, analysis and strengthening - Branco, Jorge M. (2009)
This paper aims to present an overview on the Portuguese traditional timber structures pointing out the current approach on their refurbishment.The results of an extensive survey intending to assess geometries, materials, and on site pathologies are presented. The most common traditional timber structures are analyzed, the degradation processes are reported and the main strengthening needs are discussed.